"The Celtics in the little Russia": Local expressions and representations of the clandestine communism during Francoism - Segovia Ganivet, Antonio (Hispania Nova, 2022)
This article draws lines of connections between the Communist Party of Spain´s programme strategy and effective application in the local contexts once the adoption of the Policy of National Reconciliation in 1956. By analysing the case of the comunists in a village of Granada, we small see how the implementation of these tactics consisting in “melting into the mass” positioned their organisation as the first of its kind, discovered by the police up to that point. From the cultural association “The Celtics”, the from Maracena open up new areas of interrelation representing sectors of the rural society importance that the term “small Rusia” is embedded in the popular imagination and PCE became deeply rooted among the people of his village which will remain until the nineties.
Keywords: communism; oral memory; clandestine; micro-mobilization; repression; associativism